Bimetal–organic frameworks for functionality optimization: MnFe-MOF-74 as a stable and efficient catalyst for the epoxidation of alkenes with H2O2. Issue 4 (11th January 2018) - Yuan, Kuo; Song, Tianqun; Wang, Dawei; Zou, Ye; Li, Jinfeng; Zhang, Xiaotao; Tang, Zhiyong; Hu, Wenping
Abstract : In this work, we synthesized a series of microcrystalline Mn x N100− x -MOF-74 (N = Fe, Co and Ni) materials by a one-pot reaction. Abstract : In this work, we synthesized a series of microcrystalline Mn x N100− x -MOF-74 (N = Fe, Co and Ni) materials by a one-pot reaction. Powder X-ray diffraction (PXRD) patterns of Mn x N100− x -MOF-74 matched well with those of single-metal MOF-74, and the scanning electron microscopy (SEM) images exhibited homogeneous nanocrystallites aggregated together. The amounts and dispersion of metals were analyzed by using inductively coupled plasma (ICP) and energy-dispersive X-ray spectroscopy (EDS), separately. Mn x N100− x -MOF-74 could remain crystalline and efficiently catalyze the epoxidation of alkenes in DMF with NaHCO3 and 30% H2 O2 . In particular, Mn29.39 Fe70.61 -MOF-74 can achieve almost 100% conversion for styrene with 95.0% selectivity towards styrene oxide and be reused at least five times without loss of activity.